2005
DOI: 10.46429/jaupr.v89i1-2.1071
|View full text |Cite
|
Sign up to set email alerts
|

Extractos de neem en el comportamiento de Aphis nerii y la transmisión del virus de la mancha anular del papayo

Abstract: The effect of neem extracts on feeding behavior of Aphis nerii, as well as Papaya Ringspot Virus (PRSV-p) transmission, was determined. We evaluated papaya seedlings sprayed under laboratory conditions with a 10% aqueous extract of unpeeled neem seed and with a water control. Two time periods, exploratory (0 to 3 min) and feeding (>3 to 20 min), were used to evaluate aphid feeding behavior. Aphid mortality was determined 24 h after spraying. Viral transmission was measured by ELISA tests. No significant dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Se calcula la existencia de cerca de 85 especies de plantas con potenciales propiedades de repelencia contra insectos en Latinoamérica (Ramírez-Suárez et al, 2018), con componentes específicos (Alcalá-Orozco et al, 2017). Entre estas especies, la planta neem, considerada como un producto botánico bioactivo (Hernández- Castro et al, 2005), se presenta como una alternativa (Daza y Florez, 2006), habiendo sido utilizada como repelente de insectos en plantas, contra zancudos en humanos, como garrapaticida y contra moscas (Gruber, 1992 Los resultados obtenidos en la extracción de aceite de neem son semejantes a quienes recomiendan el método soxhlet utilizando hexano (Rodríguez et al, 2012;Tesfaye y Tefera, 2017). No obstante, existen métodos que utilizan maquinaria industrial y procesos fisicoquímicos con rendimiento de 76% y con máquinas de pelletsextrusado prensado con rendimientos de 64%, pero cuyos procesos son de mayor costo (Escalante et al, 2004;Delgado et al, 2012;Cárdenas, 2017).…”
Section: Discussionunclassified
“…Se calcula la existencia de cerca de 85 especies de plantas con potenciales propiedades de repelencia contra insectos en Latinoamérica (Ramírez-Suárez et al, 2018), con componentes específicos (Alcalá-Orozco et al, 2017). Entre estas especies, la planta neem, considerada como un producto botánico bioactivo (Hernández- Castro et al, 2005), se presenta como una alternativa (Daza y Florez, 2006), habiendo sido utilizada como repelente de insectos en plantas, contra zancudos en humanos, como garrapaticida y contra moscas (Gruber, 1992 Los resultados obtenidos en la extracción de aceite de neem son semejantes a quienes recomiendan el método soxhlet utilizando hexano (Rodríguez et al, 2012;Tesfaye y Tefera, 2017). No obstante, existen métodos que utilizan maquinaria industrial y procesos fisicoquímicos con rendimiento de 76% y con máquinas de pelletsextrusado prensado con rendimientos de 64%, pero cuyos procesos son de mayor costo (Escalante et al, 2004;Delgado et al, 2012;Cárdenas, 2017).…”
Section: Discussionunclassified
“…Other works have also proved the great insecticide effect of Azadirachta indica extracts. Hernández-Castro et al [ 59 ], showed the efficiency of aqueous extract 10% w / v (10 g of plant material per 100 mL of water) of unpeeled Azadirachta indica seed in repelling the aphid Aphis nerii from feeding on papaya plants ( Carica papaya L.) sprayed with the plant extract. In addition, the aphid mortality after 24 h at the extract-sprayed plants was higher by 27% when compared to the control (only water-sprayed plants).…”
Section: Plant Extracts As Bio-insecticidesmentioning
confidence: 99%